مکالمہ۔ شرائط، ضوابط، حدود و قیود (سیرت طیبہ کی روشنی میں): Dialogue. Terms, conditions, limitations and restrictions (in the light of Sirat Tayyaba) - Dr. Syed Aziz Ul Reshman, (Seerat Studies, 2023)
Dialogue -conditions, rules and limitations in the light of Seerat e Taiyyaba SAW. We encounter many issues in this life and these issues are basically of two types. The first type of issues are those which are encountered by our predecessors with little or no difference. For this type, we have the experience and expertise of predecessors, lessons from history and books of scholars and their writings which give us clear guidelines to deal with these matters. The second type of issues are involved with continuous evaluation and modernization and we do not have any president or example set for them. For these problems we have set principles in Quran and sunnah but we do not have secondary details and guidelines available for their solution so we have to rely on ijtihad. In these matters of ijtihad the issues get more serious consideration because of the complexities and the sensitivities of the problems. There is always a chance of difference of opinion and one needs to be more careful. Those who appreciate these judgments by Ijtihad and those who use them for reference needs not to be in urgency and shall be very careful with focus on reasoning and patience to understand the reality.The topic under discussion emphasizes the carefulness of the issue and discusses different aspects of it and presents it to the World of scholars for their analysis and judgment.